Political economy and policy analysis - Merlo, Antonio (Economist) (Routledge, 2019)
Most of economics takes politics for granted. Through some (often implausible) assumptions, it seeks to explain away political structures by characterizing them as stable and predictable or as inconsequential in understanding what goes on in an economy. Such attempts are misguided, and this book shows how governments and political institutions are composed of people who respond to incentives and whose behavior and choices can be studied through the lens of economics.